Recognition and management of congenital ichthyosis in a low-income setting. Issue 8 (20th August 2019) - Saso, Anja; Dowsing, Benjamin; Forrest, Karen; Glover, Mary
Abstract : We report the case of a 3-week old girl in The Gambia who presented to hospital with an undiagnosed skin disorder evolving since birth. Using telemedicine to seek specialist dermatology advice abroad, she was diagnosed with and managed for suspected congenital lamellar ichthyosis. Poor early recognition and limited resources, for both acute and chronic care, created significant challenges to optimal management; these were overcome, in part, by adopting a common sense, back-to-basics approach to treatment and by empowering the parents to take ownership of their infant's daily skin and eye care. This case highlights key global health issues associated with managing chronic, often debilitating, paediatric dermatological conditions in a low-income setting; namely, poor access to important diagnostic tools and medications, lack of experience and expertise in the management of severe skin disease and its associated complications, absence of long-term community support, alternative health beliefs and risk of sociocultural stigma.